Analysis of biogas production from biomass residue of palm oil mills using an anaerobic batch test - Norashikin Ahmad Kamal; Siti Nooraihanah Osman; Lee, Dong Yeol; Marfiah Ab Wahid (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Malaysian palm oil industry has grown rapidly due to Malaysia’s tropical weather and suitable terrain. Palm oil production is now categorized as the most significant agriculture-based industry in the country. Along with strong economic returns, the palm oil industry also generates an abundance of waste products, including empty fruit bunches (EFB) (23%), mesocarp fibre (12%), shells (5%) and palm oil mill effluent (POME) (60%) for every batch of fresh fruit bunches (FFB) processed in the mills. This study is meant to fill the gap from previous studies in terms of biogas productions from the POME or the combination of POME and EFB which normally been conducted under the thermophilic conditions. The appropriate mixture ratios between POME and EFB in anaerobic digestion will reduce time of treatment and space if been conducted in the low temperature (mesophilic conditions). Thus, this paper is focuses on the analysis of batch test design which consist of low temperature (mesophilic, 20-40 °C) conditions for evaluating the performance of biogas production from the combination of POME and EFB in anaerobic digestion. The aim was to determine the amount of biogas production based on different ratios of POME and EFB mixtures. Biogas 1, containing 160 mL of fresh POME mixed with 40 g of EFB, was shredded and blended with 1800 mL seed sludge. Biogas 2, containing 120 mL of fresh POME mixed with 80 g of EFB, was shredded and blended with 1800 mL seed sludge. Based on the analysis of the results, the total production of Biogas 1 was greater than that of Biogas 2. The findings also show that the ratio of POME and 20% EFB (Biogas 1) was more efficient in producing the biogas compared to the ratio POME and 40% EFB (Biogas 2) under the mesophilic conditions. Thus, the mesophilic conditions required energy saving and low-cost process, compared to the previous studies which used the high temperature (thermophilic, 41-122 °C) that definitely was costly and require more energy consumption. This study will serve as preliminary results for enhancing the treatment methods use in Malaysia and form the early basis for the development of a new technology incorporating a combination of POME and EFB.